Flow-Based Optimization of Products or Devices - Basse, Nils Tångefjord (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Flow-based optimization of products and devices is an immature field compared to the corresponding topology optimization based on solid mechanics. However, it is an essential part of component development with both internal and/or external flow. The aim of this book is two-fold: (i) to provide state-of-the-art examples of flow-based optimization and (ii) to present a review of topology optimization for fluid-based problems.